The Efficient Market Hypothesis and the Implications for Financial Reporting (Book). - Buchman, Thomas A.; Meyer, Philip E. (The Accounting Review, 1983)
Abstract Reviews the book "The Efficient Market Hypothesis and the Implications for Financial Reporting," by Simon M. Keane.